Zlomenina anatomického krčku humeru spojená se zadní luxací ramene – kazuistika - Zatloukal, A; Kirpichenko, R; Lerch, M (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2016)
A rare case of a fracture of the anatomical neck of the humerus associated with a posterior dislocation of the shoulder in a 43-year-old man is presented. It was managed by immediate surgery using locking plate osteosynthesis. The shoulder was immobilised for 5 weeks in a Gilchrist brace. The outcome was very good with a full range of motion and a stable shoulder at 1 year after injury, with no signs of avascular necrosis of the humeral head. The aetiology of this injury and possibilities of its treatment are discussed. Key words: shoulder dislocation, humeral fractures.
Keywords: dospělí; Humeral Fractures; Adult; výsledek terapie; lidé; Shoulder Dislocation; Treatment Outcome; hlavice humeru; Range of Motion, Articular; luxace ramenního kloubu; Bone Plates; kostní destičky; rozsah kloubních pohybů; Male; Humeral Head; vnitřní fixace fraktury; mužské pohlaví; fraktury humeru; Fracture Fixation, Internal; Humans